Quality and safety issues in commercial building maintenance - Mohd Paren, Mohd Najib; Mohd Rafi, Nor Syazana; Jauhari, NorFadhilah; Mohd Nawi, Mohd Nasrun (2013)
This paper is concerning the quality of building services maintenance.Building services design, installation and maintenance will have a significant effect on the efficiency of the building service systems and the performance of buildings.Hence, building services maintenance must be planned and managed throughout the whole life of a project.The current management of building services maintenance is not entirely efficient and satisfactory.The application of a quality management system is seen to be a useful framework which can provide better control and significant improvements of all maintenance activities.However, the safety issues are also important in the building maintenance.Safety and health issues refer to the protection of the residents and visitors from accidents and get disease threats while in a building.The low quality of work and insufficient maintenance of a building can be a factor causing an accident, injury or death.